TULBURARĂRI PSIHICE ALE VICTIMELOR CU LEZIUNI CORPORALE - USM ADMIN (Moldova State University, 2007)
Usually medico-legal reports do not contain information concerning psychic disturbances, the evolution of which was debuted or facilitated by the physical traumatism of victims. Therefore this study is devoted to determination of psychic disturbances (acute stress, post-traumatic stress disorder, anxiety, mental depression) at persons having physical injuries. 50 persons participated in this study. These persons were the "victims of traumatism and physical injuries"who applied for the medico-legal expertise or were exposed to medico-legal expertise by the prosecuting bodies. The obtained results showed that persons having physical injuries may have psychic disturbances represent the consequences of suffered traumatism. Therefore the persons having suffered serious physical injuries represent the highest number of cases of determination of psychic disturbances.